IDENTIFIKASI GEJALA PASCA VAKSINASI COVID-19 DOSIS KE-3 (BOOSTER) PADA MAHASISWA S1 KEPERAWATAN - Hadi Saputro, Suyatno; Nuraini, Reza (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: To find out the symptoms of Post-Immunization Adverse Events (AEFI) that appear in the third Dose of COVID-19 (Booster) vaccination for nursing undergraduate students. Methods: This research design uses a quantitative descriptive research design, a population of 211, and a sample of 138 using a purposive sampling technique, the variable in this study is Post-Immunization Adverse Events (AEFI) of the third Dose of COVID-19 Vaccine (Booster). Using analytical descriptive data analysis. Results: Symptoms of AEFI that often appear after booster doses of AstraZeneca, Moderna, Pfizer, and Sinovac vaccinations are headache, fever, pain accompanied by weakness in the injected arm. Respondents who received the Moderna vaccine dominated symptoms of AEFI. Conclusion: It is hoped that this research can provide information on how to properly describe, prevent and manage AEFI symptoms